Recent Issues in the Development and Application of Targeted Therapies with Respect to Individual Animal Variability - Natalia Kurhaluk; Halina Tkaczenko (Animals)
This literature review explores the impact of molecular, genetic, and environmental factors on the efficacy of targeted therapies in veterinary medicine. Relevant studies were identified through systematic searches of PubMed, Web of Science, Scopus, and ScienceDirect using keywords such as “species-specific treatment strategies”, “signalling pathways”, “epigenetic and paragenetic influences”, “targeted therapies”, “veterinary medicine”, “genetic variation”, and “free radicals and oxidative stress”. Inclusion criteria included studies focusing on species-specific therapeutic responses, genetic influences, and oxidative stress. To ensure that only the most recent and relevant evidence was included, only peer-reviewed publications from the last two decades were considered. Each study selected for analysis was critically appraised, with a particular emphasis on methodological quality, experimental design, and scientific contribution to the understanding of how environmental and biological factors influence therapeutic outcomes. A special emphasis was placed on studies that used a comparative, cross-species approach to assess variability in therapeutic responses and potential adverse effects. The review synthesises evidence on the role of epigenetic and paragenetic factors and highlights the importance of cross-species studies to understand how environmental and biological factors influence treatment outcomes. By highlighting genetic variation, oxidative stress, and individual species differences, the review argues for personalised and species-specific therapeutic approaches. The review emphasises that such an approach would improve veterinary care and inform future research aimed at optimising targeted therapies, ultimately leading to better animal health and treatment efficacy. A key contribution of the review is its emphasis on the need for more personalised treatment protocols that take into account individual genetic profiles and environmental factors; it also calls for a greater integration of cross-species studies.